Markberedning med grävmaskin i blockrik terräng - Sahlin, Marcus (2017)
This report was made on behalf of Stora Enso Skog AB. It deals with site preparation on two clearcuts in boulder-rich terrain. Because of the rocky terrain, the scarification was made with excavators, one equipped with a wide bucket and one equipped with a narrow bucket.